Three new species of Pauropoda (Myriapoda) from Brazil with description of a new genus in Diplopauropodidae, Adelphopauropus - Scheller, Ulf (Zootaxa, 2013)
Three new species of Pauropoda are described from Brazil, Allopauropus prolongus n.sp. and Decapauropus glomeratus n.sp. in Pauropodidae, and Adelphopauropus ichtyematos n. gen., n. sp. in Diplopauropodidae.